Utilization of Assessment Features in Platform Merdeka Mengajar (PMM) in the Assessment of Indonesian Language Learning - Firdaus Aritonang; Iqbal Syahrul Akbar Al Aziz; Sarwiji Suwandi (Graduate School of Universitas Negeri Malang, 2023)
The Indonesian government has launched the Merdeka Teaching Platform (PMM) application with various features that support learning activities in the independent curriculum. One of them is the student assessment feature. This study aims to determine the use of assessment features in PMM. This study used a qualitative descriptive method with interview, documentation, and observation techniques. The results of the study show that PMM has positive benefits in helping educators carry out assessments. Assessments in PMM include formative, summative, and diagnostic assessments that can be adjusted and adapted, so that PMM can be one of the solutions that educators can use in the era of independent curriculum, both in the assessment process and when conducting learning